Regreening Africa: Consolidated Baseline Survey Report - Hughes, K.A.; Oduol, J.; Kegode, H.; Ouattara, I.; Vågen, Tor-Gunnar; Winowiecki, Leigh Ann; Bourne, M.; Neely, C.L.; Ademonla, D.; Schoubroeck, F. van; Chomba, S.; Carsan, S. (World Agroforestry Centre, 2020)
The United Nations General Assembly declared 2021 to 2030 as the decade of ‘ecosystem restoration’, signalling a global consensus on the urgency to restore degraded lands. Restoring degraded lands is critical to regain lost ecological functionality that underpins life-sustaining ecosystem services, such as the provision of food, fresh water, and fibre, and the regulation of climate, natural disasters, and pests. Indeed, restoration is fundamental for meeting the triple goals of tackling the climate crisis, reversing biodiversity loss, and improving human wellbeing. Regreening Africa (2017 to 2022) is part of a larger global and regional effort to reverse and halt land degradation, which is being implemented in eight African countries: Ethiopia, Ghana, Kenya, Mali, Niger, Rwanda, Senegal, and Somalia.